Long COVID-19 and Postural Orthostatic Tachycardia Syndrome- Is Dysautonomia to Be Blamed? - Chadda, Karan R.; Blakey, Ellen E.; Huang, Christopher L. -H.; Jeevaratnam, Kamalan (Frontiers in Cardiovascular Medicine, 2022)
While the increased arrhythmic tendency during acute COVID-19 infection is recognised, the long-term cardiac electrophysiological complications are less well known. There are a high number of patients reporting ongoing symptoms post-infection, termed long COVID. A recent hypothesis is that long COVID symptoms could be attributed to dysautonomia, defined as malfunction of the autonomic nervous system (ANS). The most prevalent cardiovascular dysautonomia amongst young people is postural orthostatic tachycardia syndrome (POTS). Numerous reports have described the development of POTS as part of long COVID. Possible underlying mechanisms, although not mutually exclusive or exhaustive, include hypovolemia, neurotropism, inflammation and autoimmunity. Treatment options for POTS and other long COVID symptoms are currently limited. Future research studies should aim to elucidate the underlying mechanisms of dysautonomia to enable the development of targeted therapies. Furthermore, it is important to educate healthcare professionals to recognise complications and conditions arising from COVID-19, such as POTS, to allow prompt diagnosis and access to early treatment.